(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
Samples were taken from 70 springs in Gallaorol district, Jizzakh region of Uzbekistan, and their physical properties (smell, color level, turbidity, precipitation, clarity) were checked in the water laboratory.